2014
DOI: 10.1186/1472-6831-14-49
|View full text |Cite
|
Sign up to set email alerts
|

One year survival of ART and conventional restorations in patients with disability

Abstract: BackgroundProviding restorative treatment for persons with disability may be challenging and has been related to the patient’s ability to cope with the anxiety engendered by treatment and to cooperate fully with the demands of the clinical situation. The aim of the present study was to assess the survival rate of ART restorations compared to conventional restorations in people with disability referred for special care dentistry.MethodsThree treatment protocols were distinguished: ART (hand instruments/high-vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
13
0
3
Order By: Relevance
“…ART was presented to the World Health Organization in 1994 as a new approach to treat dental caries (Frencken et al , ). The technique consists of the excavation and removal of the softest portions of carious lesions using hand instruments only and restoration with fluoride containing glass ionomers (Molina et al , ). Previous studies in a high‐risk population showed that glass ionomer vs. amalgam restorations plus daily application of fluoride in xerostomic patients did not present recurrent caries but the patients treated with amalgam without fluoride developed recurrent caries (Haveman et al , ).…”
Section: Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…ART was presented to the World Health Organization in 1994 as a new approach to treat dental caries (Frencken et al , ). The technique consists of the excavation and removal of the softest portions of carious lesions using hand instruments only and restoration with fluoride containing glass ionomers (Molina et al , ). Previous studies in a high‐risk population showed that glass ionomer vs. amalgam restorations plus daily application of fluoride in xerostomic patients did not present recurrent caries but the patients treated with amalgam without fluoride developed recurrent caries (Haveman et al , ).…”
Section: Questionsmentioning
confidence: 99%
“…Oral diseases in HIV-infected children E Arrive et al restoration with fluoride containing glass ionomers (Molina et al, 2014). Previous studies in a high-risk population showed that glass ionomer vs. amalgam restorations plus daily application of fluoride in xerostomic patients did not present recurrent caries but the patients treated with amalgam without fluoride developed recurrent caries (Haveman et al, 2003).…”
Section: Oral Diseasesmentioning
confidence: 99%
“…Ethical approval was obtained from the local Ethical Committee, CIEIS Facultad de Odontología, Universidad Nacional de Córdoba with the reference number 38/2012 and the trial was registered at Netherlands Trial Register with number 4400. As a detailed report about the methodology used is presented elsewhere, 21 a shortened version is presented underneath.…”
Section: Methodology Ethicsmentioning
confidence: 99%
“…The survival rates have been recently published and showed a 98% survival of all ART high-viscosity glass-ionomer restorations and a 91% survival of all conventional composite restorations after one year. 21 The present study, the first in its kind, is aimed to compare ART with conventional restorative treatment in terms of acceptability and feasibility of the approach and respondent satisfaction in a population of patients referred for special care restorative dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…Так, при использовании методики для лечения лиц с задержкой интеллектуального развития она оказалась более эффективной, чем стандартное лечение с применением композитных материалов (соответственно 97,8±1,0% против 90,5±3,2% успешных результатов через 1 год наблюдения), именно благодаря лучшему сотрудничеству больных, а также большей толерантности стеклоиономерных цементов к погрешностям в изоляции рабочего поля от влаги. Полноценного высушивания полости у этой группы больных добиться сложно из-за непроизвольных движений языка и обильного слюнотечения [9].…”
Section: стоматология 4 2015unclassified